Tectonic dynamics shaping the lake Hazar Basin along the East Anatolian fault system: Insights from fault kinematics and structural evolution - Akgun, Elif; Softa, Mustafa (Science Press, 2026)
The Lake Hazar basin, located along the Palu segment of the East Anatolian Fault System (EAFS), provides a key natural laboratory for examining transtensional deformation in a major intracontinental strike-slip zone. Integrated field mapping, fault-slip analysis, and focal mechanism inversion reveal a polyphase tectonic history involving sequential compressional, strike-slip, and extensional regimes. Rigorous discrimination of heterogeneous fault-slip datasets into homogeneous subsets enabled reconstruction of geologically consistent stress tensors and clarified the temporal transition from strike-slip to transtensional deformation. Paleostress results indicate NNE-SSW compression and NW-SE extension, consistent with present-day seismotectonic and geomorphic patterns. Variations in stress ratio R-values (0.26-0.57 for strike-slip; 0.28-0.33 for extensional domains) and low misfit angles (<15 degrees) reflect localized strain partitioning and reactivation of inherited faults. The Lake Hazar basin thus evolved from a pull-apart structure into a negative flower geometry through successive deformation and fault linkage. These findings highlight that discriminating polyphase fault-slip data is essential for resolving deformation dynamics in complex fault systems. The integrated structural, paleostress, and seismotectonic framework presented here refines understanding of strain localization, fault reactivation, and stress transfer along the East Anatolian Fault System.
Keywords: Palu segment; East Anatolian Fault System; Lake Hazar basin; Paleostress; Strain partitioning; Fault reactivation